Classroom creative encounters springboard to inquiry in social studies in grade six fast learners - Caracena, Angelina Ybañez (1974)
The purpose of the study is to find out how classroom creative encounters can be utilized as springboards to inquiry in social studies for grade six fast learners. It also seeks to know the theoretical foundations of classroom creative encounters and inquiry, the distinguishing characteristics of an inquiry-oriented classroom, the role of the teacher in fostering a climate conducive to the development of inquiry, the way by which classroom creative encounters can lead to inquiry in social studies and lastly, the materials or episodes that may be used to initiate these classroom creative encounters for grade six fast learners.